TARGETED THERAPIES AND IMMUNOTHERAPY IN ADVANCED NON-SMALL CELL LUNG CANCER – CURRENT STANDARDS AND NEW DIRECTIONS - Patrycja Krysiak; Artur Marcysiak; Aleksandra Marcysiak; Michał Stermach; Nina Kubikowska; Iga Poprawa; Małgorzata Landowska; Filip Komar (International Journal of Innovative Technologies in Social Science, 2026)
Non-small-cell lung cancer (NSCLC) remains the leading cause of cancer-related mortality, but advances in targeted therapies and immunotherapy have radically changed the prognosis of advanced disease. The introduction of tyrosine kinase inhibitors directed against alterations in EGFR, ALK, ROS1, BRAF, MET, RET, KRAS G12C, NTRK, HER2 and other genes has led to a shift away from uniform chemotherapy toward treatment based on precise molecular characterization of the tumor. In parallel, immune checkpoint–blocking antibodies, primarily targeting PD-1/PD-L1 and CTLA-4, have become the standard of care in first and subsequent lines of treatment for patients without oncogenic drivers, used both as monotherapy and in combination with chemotherapy and anti-angiogenic agents.Despite substantial survival gains, most patients develop primary or acquired resistance to targeted therapy and immunotherapy, which represents a major clinical challenge. This article reviews current standards of care in advanced NSCLC, emphasizing the role of molecular testing and PD-L1 assessment in therapy selection, the place of combination regimens including immune checkpoint inhibitors, and emerging strategies to overcome resistance, such as next-generation inhibitors, bispecific antibodies, antibody–drug conjugates, neoantigen vaccines and cellular therapies. Particular attention is given to future perspectives for further personalization of treatment, the role of predictive biomarkers (including PD-L1, TMB and ctDNA), and ongoing and planned studies of combination approaches that may further improve outcomes for patients with advanced NSCLC.